Estratégias de forrageamento de beija-flores (aves : Trochilidae) em relação à densidade de recursos florais de Palicourea rigida Kunth (Rubiaceae) - Nunes, Carlos Henrique (2011)
Nunes, C.H. Assembly and foraging behavior of hummingbirds and their relation to spatial distribution of floral resources Palicourea rigida Kunth (Rubiaceae). Hummingbirds are birds restricted to the Americas and are the main birds to explore the floral nectar in these regions. Palicourea rigida belongs to Rubiaceae family and has wide distribution in the Cerrado. It has characteristics clearly ornithophilous. The aim of this study was to determine how the spatial distribution of P. rigida affects assemblage and behavior of the hummingbirds that use it as food resource. The study was conducted at the Private Ecological Reserve of Clube Caça e Pesca Itororó Uberlândia, Brazil. We established three transects of 460 meters long, starting perpendicular to the “vereda” palm swamp edge going into the cerrado, to cover the gradient of spatial distribution presented by P. rigida. We defined three sampling points per transect called proximal, medial and distal according to the proximity of the “vereda”. A census of P. rigida individuals was conducted on each point in October 2009. The nectar production was obtained in December 2010. The observations of hummingbirds were carried out between November 2009 and January 2010 from 7 to 11 am hours, totaling 94.5 hours of observation. We recorded the date, weather conditions, time, kind of visitor, number of flowers and inflorescences visited, time spent foraging, and agonistic encounters. At the end of each day's observation were quantified the number of flowering individuals, flowers per inflorescence and inflorescence per individual at each sample point. The data indicated a gradient in the number of P. rigida individuals and open flowers. These were higher in proximal points and lower in distal points. The transects did not differ in the number of individuals of P. rigida, but there was difference among the three kinds of points The were no marked differences between flowering peaks of P. rigida among the sample points. The average production of nectar per flower was 9.41±1.94 with a mean sugars concentration of 24±1.5%, representing an average calorie supply per flower of 0898± 0.072 cal /μl. The amount of calories was higher at proximal points and lower at the distal ones. We recorded eight hummingbird species visiting the flowers.We made 307 records and the most frequent species was Eupetomena macroura with 30% of the records, besides having been seen visiting the greatest total number of flowers (n = 903) and inflorescences (n = 283). However, Phaethornis pretrei was the species with largest average number of inflorescences and flowers visited per record. The species P. pretrei exhibited also the highest average time of visit. However, the greatest average defense time was observed for E. macroura. There was positive correlation between the number of individuals of P. rigida, estimated caloric value available, number of flowers in anthesis, total time of visits, number of records of flower visitors and time of defense. The number of flowers visited was different between the proximal and distal points and between medial and distal points. Fewer flowers were visited at distal points. There were observed also differences in the number of records between the proximal points in relation to the medial and distal points. There were no differences in the total time of visits between the proximal, medial and distal points. The number of agonistic encounters differed between proximal points in relation to the medial and distal, with the number of agonistic encounters higher in sections closest to the “vereda” edge than in the farthest points of the trails. We recorded 136 agonistic encounters with 44 intra-specific encounters. Three species were donors/agents? of agonistic actions: E. macroura, A. fimbriata and C. serrirostris. E. macroura was the most aggressive species and the most frequent response to aggression was escape. Changes of agonistic actions donor species were observed in some points on all three transects. This study confirmed the distribution pattern of P. rigida, demonstrated to be common throughout the area of CCPIU reserve. All species were recorded in proximal points, that there was a greater availability of resources. The richness of hummingbirds in the area is related to the abundance of flowers. Spatial distribution of floral resources influenced the hummingbirds assemblage that used the nectar offered, and especially their foraging behavior.